Impaired consciousness, hypokalaemia and renal tubular acidosis in sustained Nurofen Plus abuse. Issue 11 (27th November 2019) - Li, Rebecca; Hasan, Neda; Armstrong, Luke; Cockings, Jerome
Abstract : Ibuprofen-induced renal tubular acidosis is a rare but important diagnosis which should be considered in patients presenting with hypokalaemia and metabolic acidosis. This case report details the case of a 33-year-old woman presenting with reduced conscious state, metabolic acidosis and profound hypokalaemia without an obvious cause. With correction of the patient's electrolyte and acid-base disturbance, her conscious state improved allowing disclosure of her use of Nurofen Plus for its euphoric opiate effects. The diagnosis of renal tubular acidosis had been considered and subsequent disclosure of excessive chronic ingestion of ibuprofen suggested this to be the underlying cause. The striking feature of our patient was the insidious development of the problem and delayed accurate drug history. An important safety message arising from our case is the composite risk of dependence on the opiate component of over the counter analgesics, such as Nurofen Plus, and adverse events related to the ibuprofen component.